THE IMPLEMENTATION OF CHAIN STORY GAME TO TEACH SPEAKING IN RECOUNT TEXT FOR EIGHTH GRADERS OF SMPN 39 SURABAYA (RETAIN, 2016)
THE IMPLEMENTATION OF CHAIN STORY GAME TO TEACH SPEAKING IN RECOUNT TEXT FOR EIGHTH GRADERS OF SMPN 39 SURABAYA Kharisma Narendra English Education Faculty of Languages and Arts State University of Surabaya unesakharisma@gmail.com Drs. Fahri, M.A. English Education Faculty of Languages and Arts State University of Surabaya fahri@unesa.ac.id Abstrak Penelitian ini fokus pada penerapan Chain Story Game untuk Mengajarkan Speaking dalam Recount text . dan tujuan dari penelitian ini adalah untuk memberikan penjelasan yang jelas tentang mengajarkan Speaking melalui Chain Story Game . Penggambaran nya meliputi : (1) Bagaimana Chain Story Game di terapkan dalam mengajarkan Speaking Dalam bentuk Recount text pada siswa kelas delapan di SMPN 39 Surabaya, dan (2) bagaimana siswa-siswa merespon penerapan Chain Story Game pada pengajaran Speaking dalam Recount text. Penulis menerapkan penelitian qualitative dan menggunakan 2 instrumen penelitian ,yakni : Lembaran Observasi dan kuesioner. Hasil dari penelitian ini menunjukan bahwa Penerapan Chain Story Game untuk Mengajarkan Speaking Dalam Recount text pada siswa kelas delapan di SMPN 39 Surabaya sudah di lakukan dengan sangat baik. Itu terlihat dari tahap awal aktifitas ,selama aktifitas, hingga pada akhir aktifitas. Sehingga respon para siswa terhadap materi pembelajaran Recount text dari guru juga sangat baik. Dan para siswa merasa lebih mudah menerima materi dengan metode cooperative learning yang di terapkan dalam dalam bentuk Chain Story Game. Dengan Chain story game, para siswa menunjukan keberanian untuk tampil dalam proses belajar mengajar, yang mana di tunjukan dari keaktifan siswa untuk tampil di depan kelas untuk bercerita dan membangun kepercayaan diri dalam menyampaikan pendapat dalam kelompok mereka. Chain Story Game membuat siswa merasa menikmati dalam memahami materi pelajaran recount text. Kata Kunci : Speaking,Recount text,Game,Chain story game Abstract This research focuses on the implementation of Chain story game to teach speaking in Recount text. And, the purpose of this research is to give the brief explanation about teaching speaking trough Chain story game . The description includes: (1) How is “Chain Story Game” implemented in teaching speaking in the form of recount text to the eight graders of SMPN 39 Surabaya, and (2) How are the students response the implementation of chain story game in teaching speaking in recount text to the eighth graders of SMPN 39 Surabaya. The writer applies qualitative research and uses 2 research instruments, they are: observation sheet and questionnaire. The result of this research shows that The implementation of chain story game to teach speaking for eighth graders of SMPN 39 surabaya had done very well. It showed from the stage of Pre-Activity until Post-Activity.Then, the students were very good in response the lesson material of Recount text from the teacher. The students perceived easier when they received the material by using Cooperative Learning method which implemented in the form of chain story game. By Chain story game, the students showed the bravery in the teaching-learning process. It showed from the students were active in performing in front of the class to tell story and developing confidence in delivering opinion in their group. Chain story game made the students perceived enjoy in understanding the lesson material of Recount text. Key Words: Speaking, Recount text,Game,Chain story game